Environmental social responsibility: research trends - Eslava Zapata, Rolando; Sánchez Castillo, Verenice; Sierra Narváez, Francisco (Ingeniería Solidaria, 2025)
Introduction: The environment is facing a significant crisis due to pollution caused by human and industrial activities. The use of fossil fuels and improper solid waste management are major contributors to environmental degradation. This article is the result of the research project “Leadership and Financial Performance in the Colombian Clay Sector,” developed at the Universidad Libre Colombia Seccional Cúcuta in 2024.Problem: Environmental Social Responsibility (ESR) refers to the actions companies take to protect the environment. A company is considered socially responsible if it commits to environmental sustainability and adopts practices that ensure the efficient management of resources.Objective: The aim of this study is to analyze the current trends in research related to Environmental Social Responsibility.Methodology: A bibliometric analysis was conducted using data from the Scopus database and analyzed with the VOSviewer software.Results: The analysis of the keywords led to the generation of two distinct clusters. The first, represented in red, is related to green policies, while the second, identified in green, focuses directly on Environmental Social Responsibility.Conclusion: Current research trends are primarily focused on environmental performance, ESG (Environmental, Social, and Governance), and the effects of COVID-19. These trends highlight the shift towards sustainable behaviors, promoting environmentally friendly practices and establishing policies that strengthen pro-environmental attitudes and increase environmental awareness.Originality: This research introduces new insights into the trends in Environmental Social Responsibility, using a novel search engine that enables the identification of new clusters.Limitations: The study relies exclusively on data from the Scopus database and does not incorporate other databases for a broader perspective.